Peranan Strategi Pemasaran Produk Fulnadi Dalam Upaya Meningkatkan Penjualan pada Asuransi Takaful Keluarga Palembang - Sakinah Sakinah; Nur Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
The focal point of exploration analyzed in this last attempt is the work of the day-to-day goods promotion system with the aim of establishing a Palembang family takapul protection agreement. In this review the author uses subjective exploration, which describes the information obtained from the field related to the examination problem above. Observing the things above, this review uses a subjective expressive technique which is expected to describe or describe circumstances or oddities such as during exam hours, more precisely introducing information about the full blown goods promotion methodology by PT Asuransi Takaful. Palembang Branch Family. The method of gathering information in this review utilizes perceptions, encounters and documentation. This exploration concludes that the showcasing all out item technique by PT Asuransi Takaful Keluarga Palembang Branch uses two procedures, namely: First, the methodology which is a system for its implementation in the actual organization, as far as working on the nature of HR for advertisers to become proficient advertisers by leading exams, inspiration, and territorial assessments. Second, procedures outside the province. Second, the outside methodology in its application is completed by advertisers when selling goods, such as how to manage future clients, introduction of goods, great correspondence and exchange. The execution of this system in the field is extraordinary, as evidenced by the increasing number of regular clients by PT Asuransi Takaful Keluarga Palembang Branch.